Studies of magnetotail dynamics and energy evolution during substorms using MHD simulations - S. Brogl; R. E. Lopez; M. Wiltberger; H. K. Rassoul (Annales Geophysicae, 2009)
We examine the distribution and propagation of energy in the plasma sheet and lobes using observations and simulations for three substorms. The substorms occurred on 9 March 1995, 10 December 1996, and 27 August 2001 and have been simulated using the Lyon-Fedder-Mobarry magneto-hydrodynamic code. All three events occur over North America and show a clear substorm current wedge over the ground magnetometer chains of Alaska, Canada, and Greenland. The three simulations show the thinning of the plasma sheet during the growth phase of the event and an increase in the relative amount of thermal energy due to the compression of the plasma sheet. Generally, the total lobe energy, polar cap flux, and lobe magnetic field strength simultaneously increase during the growth phase, and polar cap flux and total lobe energy only start dropping at substorm onset, as measured by the CANOPUS magnetometer chain. Starting at time of onset and continuing throughout the expansion phase a transfer of magnetic energy from the lobes into the plasma sheet occurs, with the increase in the plasma sheet energy ranging from 30–40% of the energy that is released from the lobes.